Boosting low-temperature activity and thermal stability in light alkane oxidation by balancing confined Ru species and the MFI zeolite microenvironment - Jingjing Wang; Lianghui Xia; Yanfei Jian; Qiyuan Liu; Yujie Liu; Yani Wu; He Xu; Yaruo Zhao; Jingyao Wang; Zeyu Jiang; Jinghang Huo; Yanke Yu; et al. (Chemical Engineering Journal, 2026)

Microbial co-occurrence network and spatial metabolism underlie wheat cultivar effects on medium-high temperature Daqu fermentation - Yanke Shi; Hongkui He; Mengyao Niu; Yijun Fan; Miao Yu; Yesheng Ma; Peng Wang; Zengming Gao; Xiaoxue Chen (Food Research International, 2026)

Proteomics-decoded capture kill mechanism of CuAgOx/UiO-66-NH2 for dark inactivation of pathogenic bacteria - Jiali Zhang; Yuqiu Huang; Yanke Yu; Lianghui Xia; Yanpeng Li (Journal of Hazardous Materials, 2026)

Corrigendum to “Main lipid sources affecting key aroma volatile compounds in Chinese native chicken” [Food Chemistry 474 (2025) 142990] - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Promotional antibacterial performance under dark conditions by silver induced oxygen adsorption and charge transfer - Jiali Zhang; Lianghui Xia; Luyao Zhao; Yanke Yu; Yanpeng Li (Journal of Environmental Chemical Engineering, 2025)

Main lipid sources affecting key aroma volatile compounds in Chinese native chicken - Yanji Chen; Yongli Wang; Yanke Wang; Na Luo; Richun Cai; Yang Yu; Xu Zhang; Jinmei Zhu; Guiping Zhao; Jie Wen; Huanxian Cui (Food Chemistry, 2025)

Synergistic construction of efficient heterojunction structures through vacancy engineering and nanoscale effects to enhance photodegradation efficiency - Qingyang Pang; Chaoyue Zheng; Youlin Wu; Xuan Wang; Yachong Wang; Yanke Yang; Teng Li; Canzhong Lu; Yiming Xie; Fuda Yu (Journal of Water Process Engineering, 2025)

Facile synthesis of Metal-Organic Framework/Chitosan cryogel as a robust Scavenger for Diclofenac sodium - Yanke Shi; Lijin Huang; Yu Bai; Lei Ouyang; Huiyu Zhao; Xinquan Wang; Qin Shuai (Chemical Engineering Journal, 2024)

Population pharmacokinetics and pharmacodynamics of efmarodocokin alfa (IL-22Fc) - Yanke Yu; Michael E. Rothenberg; Han Ting Ding; Ari Brekkan; Gizette Sperinde; Brandon Harder; Rong Zhang; Ryan Owen; Nastya Kassir; Annemarie N. Lekkerkerker (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Effect of morphology and simultaneous sulfation on Fe doped CeO2 for selective catalytic reduction of NO with NH3 - Jinxiu Wang; Yuqiu Liu; Xianfang Yi; Yanting Chen; Yanke Yu; Jinsheng Chen (Fuel, 2023)

Flood Wave Superposition Analysis Using Quantitative Matching Patterns of Peak Magnitude and Timing in Response to Climate Change - Qiumei Ma; Lihua Xiong; Chong-Yu Xu; Rongrong Li; Changming Ji; Yanke Zhang (Water Resources Management, 2021)

Spatiotemporal patterns of satellite precipitation extremes in the Xijiang River Basin: From statistical characterization to stochastic behaviour modelling - Qiumei Ma; Changming Ji; Lihua Xiong; Yi Wang; Chong‐Yu Xu; Yanke Zhang (International Journal of Climatology, 2021)
Given the threats from rainstorm events that have been intensified due to climate change, the investigation of heavy/extreme precipitation is attracting increasing attention. The investigation of extreme precipitation, with its restricted tools and data, is quite different from that of nonextreme precipitation. Satellite precipitation estimates (SPEs) are promising precipitation measurements due to fine spatial resolution. However, the spatiotemporal patterns of SPE extremes remain unclear. Therefore, this study attempted to systematically analyse the spatiotemporal patterns of extreme SPEs provided by the Tropical Rainfall Measurement Mission (TRMM) research product from statistical characterization to stochastic behaviour modelling. The statistical characterization was depicted using comprehensive extreme precipitation indices (EPIs), while the stochastic behaviour was modelled using the generalized Pareto distribution (GPD) to fit the ‘peak over threshold’ samples and employing the max‐stable process to fit the ‘block maximum’ samples (Max: annual 1‐day maximum, RX1day: monthly 1‐day maximum, and RX5day: monthly 5‐day maximum) of the TRMM data. The TRMM extremes were analysed across the Xijiang River Basin, China. The results of the statistical characterization revealed that compared with gauge precipitation, most TRMM EPIs were discovered to have higher temporal dynamic levels. Moreover, the spatial median of the return level for each return period derived from temporal TRMM extreme modelling with the GPD was lower than that from gauge extremes. The spatial dependence of Max in TRMM was weaker than that of either RX1day or RX5day, primarily due to different precipitation‐generating processes existing between two extreme events at annual scale compared with monthly scale. Each of the Max, RX1day, and RX5day in TRMM exhibited stronger spatial dependence than that in gauge extreme precipitation, maybe related to the area‐average‐based representation of the SPEs. These findings can enhance our insight into the spatiotemporal patterns of extreme satellite precipitation, which is beneficial for operational flood risk management.

Correction to: Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)

Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen; Peilong Yu (Climate Dynamics, 2020)
Based on the daily ERA-Interim reanalysis, interactions between the winter North Pacific storm track (WNPST) and the East Asian trough (EAT) on the interannual scale are further explored from the perspective of energy conversion and the simplified quasi-geostrophic potential vorticity equation. There is a prominent out-of-phase relationship between the EAT and WNPST on the interannual scale. It is baroclinic energy conversion rather than barotropic energy conversion that is the main physical process that the EAT affects the WNPST. When the EAT is intensified, the energy conversion from mean available potential energy to eddy available potential energy decreases; further, the energy conversion from eddy available potential energy to eddy kinetic energy is attenuated, which leads directly to remarkable weakening in the strength of the WNPST in its peak area and the region west of the date line. In addition, when the WNPST is enhanced, the WNPST dynamic forcing contributes to lowering the geopotential height near the EAT and thus profits to recover the strength of the EAT, while the thermal forcing of WNPST is opposite. However, their joint effect is still to strengthen the EAT, indicating that the impact of WNPST dynamic forcing on the EAT is stronger than that of thermal forcing. The interaction between the WNPST and EAT may be a way for the WNPST to maintain itself.

A physiological model of granulopoiesis to predict clinical drug induced neutropenia from in vitro bone marrow studies: with application to a cell cycle inhibitor - Wenbo Chen; Britton Boras; Tae Sung; Yanke Yu; Jenny Zheng; Diane Wang; Wenyue Hu; Mary E. Spilker; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Physiologically Based Pharmacokinetic Modeling and Simulation of Sunitinib in Pediatrics - Yanke Yu; Steven G. DuBois; Cynthia Wetmore; Reza Khosravan (The AAPS Journal, 2020)

Influence of cumulus convection schemes on winter North Pacific storm tracks in the regional climate model RegCM4.5 - Minghao Yang; Yanke Tan; Xin Li; Xiong Chen; Chao Zhang; Peilong Yu (International Journal of Climatology, 2020)
Based on the regional climate model RegCM4.5 driven by National Centers for Environmental Prediction (NCEP) reanalysis, the influence of cumulus convection schemes (CCSs) on the winter North Pacific storm track (WNPST) is investigated. It is found that the climatology, interannual variation, spatial modes and characteristic indices of the WNPST are extremely sensitive to the choice of CCS. Among the selected CCSs, WNPST climatology and interannual variation in the Kuo scheme are better than in other CCSs, with a smaller root mean square error. The WNPST spatial modes and strength indices in the Kuo and Grell schemes are more consistent with NCEP reanalysis. The Kuo scheme has a stronger ability to simulate the WNPST latitude index and the interannual variation of winter characteristic indices. In addition, we attempt to reveal the possible reasons for the different performances of CCSs from the viewpoint of baroclinic energy conversion (BCEC). It is found that the energy conversion from the mean available potential energy to the eddy available potential energy (BCEC1) has no significant difference among the Kuo, Grell and Emanuel schemes, while energy conversion from the eddy available potential energy to eddy kinetic energy (BCEC2) in the Kuo scheme is obviously better than other CCSs, which means that the differences in BCEC2 among these CCSs may be one of the key reasons affecting the simulation results of the WNPST.

New Insight into the Effect of Potassium on Commercial SCR Catalyst: Promotion of Thermal Stability - Yanke Yu; Xiaoran Meng; Jinsheng Chen; Jinxiu Wang; Yanting Chen (Water, Air, & Soil Pollution, 2015)

Chlorobenzene Destruction over Mesostructured CuO and MnO x Co-Modified CeO2 Catalyst: Activity and Activation Route - Chi He; Gaoshan Men; Yanke Yu; Hua Pan; Bitao Xu (Water, Air, & Soil Pollution, 2015)

Applications of Human Pharmacokinetic Prediction in First-in-Human Dose Estimation - Peng Zou; Yanke Yu; Nan Zheng; Yongsheng Yang; Hayley J. Paholak; Lawrence X. Yu; Duxin Sun (The AAPS Journal, 2012)

Examination of the Pharmacokinetics of Active Ingredients of Ginger in Humans - Yanke Yu; Suzanna Zick; Xiaoqin Li; Peng Zou; Benjamin Wright; Duxin Sun (The AAPS Journal, 2011)